Analisa Kandungan Boraks Pada Makanan Menggunakan Indikator Kubis Ungu (Brassica Oleracea L) - Odilia Dea Christina; Movi Yoga Supriyadi (Indonesian Journal on Medical Science, 2022)
The species Brassica oleracea L is known as cabbage or cabbage. This purple cabbage has a distinctive color that is purple. The purple color is caused by the presence of color pigments, namely anthocyanins, and this substance will be used as an indicator of borax. Borax is often misused to be mixed into food in order to get savory, chewy, and durable food, even though borax compounds are actually dangerous for consumption. This study aims to determine whether purple cabbage (Brasicca oleracea L) is effectively used as an identification of borax compounds. Purple cabbage extract can be used as a qualitative test to identify borax compounds, it can be characterized by the change of purple color to green color. The results of the stick color test as a borax indicator at 12 hours and 16 hours immersion. Tissue color test results as an indicator of borax in immersion